Historical continuity in the emergence of modern Hebrew - Reshef, Yael (Lexington Books, 2019)
"Historical Continuity in the Emergence of Modern Hebrew argues that due to unconventional linguistic processes in the early years of revernacularization, apparent resemblance to classical Hebrew does not necessarily reflect continuity, and apparent dissimilarity does not necessarily reflect change"--